2018
DOI: 10.1111/jfs.12614
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Staphylococcus aureus and Escherichia coli in milk by different processing sequences of ultrasound and heat

Abstract: Different processing sequences of ultrasound and heat were applied for the inactivation of Staphylococcus aureus and Escherichia coli in milk. The changes in whey protein content, particle size, zeta potential, pH, viscosity, and color values were studied to evaluate the effects on the quality of milk. Results indicated ultrasound treatment (600 W, 5 min) with postheating (63 °C 5 min) reduced S. aureus and E. coli by 1.58 and 2.02 log cfu/ml, respectively, but yielded 0.26 and 0.19 log cfu/ml sublethal S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Colour is the key quality characteristic of dairy products, which is related to the dispersion of casein micelles and fat globules in the visible spectrum (Li et al . 2019). The results of the colour values of the yoghurt samples and the colour difference are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colour is the key quality characteristic of dairy products, which is related to the dispersion of casein micelles and fat globules in the visible spectrum (Li et al . 2019). The results of the colour values of the yoghurt samples and the colour difference are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…The colour improvement of sonicated dairy products attributed to the improvement of homogenisation and light reflection which modified by the reduction of fat globules size and denaturation of soluble proteins (Li et al . 2019). Heat treatment at 65 and 90 ºC resulted in a Maillard reaction, but ultrasound had a discolouration effect on samples and decreased the yellowness value of samples and their colour scores.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the commonly used ultrasonic horns have only one transmitter on the tip, which transfers nearly all the energy through one direction. In our previous study, it was found that the TS, combined with single-direction ultrasonic radiation (600 W) and 63 • C, resulted in less than 99% reduction of S. aureus for 5 min (Li et al, 2019). Individual heat exposure has been reported to activate protective systems in bacteria cells, which could compromise the microbial inactivation level (Liu et al, 2020;Wu et al, 2021).…”
Section: Inactivation Of S Aureus Cocktail In Milk By 360-degree Radiation Thermosonicationmentioning
confidence: 99%
“…Other authors reported a partial or complete inactivation for other enzymes, such as proteases from P. fluorescens (110), pectin methyl-esterase (29,77,139), papain (86), trypsin (85), alkaline phosphatase (42), lactoperoxidase (42,66,81), lipase (42), and polyphenoloxidase (108). Few enzymes were found resistant or not affected by HPH, such as trypsin (82,83) and a protease from Rhizomucor miehei (81).…”
Section: High Pressure Homogenizationmentioning
confidence: 99%